2015
DOI: 10.4311/2013es0120
|View full text |Cite
|
Sign up to set email alerts
|

Traces of Earthquates in the Caves: Sakarlak Ponor and Kepez Cave, Mersin, (Southern Turkey)

Abstract: Abstract:The study area is located in the central part of the Taurus Mountains, where karstification is widespread and strongly influenced by tectonic rise of the region and sealevel changes in the Mediterranean Sea during the Pleistocene. Young karstification in the area was largely affected by NE-SW trending left-lateral strike-slip faults and NW-SE trending discontinuities. The general extension of discontinuities is perpendicular to the faulting direction indicated by evaluation of the caves with the digit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The obtained value is quite different from the mean rates recognized in the literature that vary between 0.015 and 0.37 mm yr −1 (e.g., White, 2007;Akgöz and Eren, 2015, and references therein). This may be explained by variations in the growth rate of stalagmites, as well as by complexities in their structure, texture, and chemical composition (e.g., Akgöz and Eren, 2015) or by peculiar geochemical processes governing the cave environment. Moreover, the observed evidence of surface erosion and internal cavities in several stalagmites strongly suggests the occurrence of periods with a slow rate of calcite accumulation and falling-drop erosion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained value is quite different from the mean rates recognized in the literature that vary between 0.015 and 0.37 mm yr −1 (e.g., White, 2007;Akgöz and Eren, 2015, and references therein). This may be explained by variations in the growth rate of stalagmites, as well as by complexities in their structure, texture, and chemical composition (e.g., Akgöz and Eren, 2015) or by peculiar geochemical processes governing the cave environment. Moreover, the observed evidence of surface erosion and internal cavities in several stalagmites strongly suggests the occurrence of periods with a slow rate of calcite accumulation and falling-drop erosion.…”
Section: Discussionmentioning
confidence: 99%
“…This evidence includes broken speleothems and fallen stalactites (e.g., Postpischl et al, 1991;Ferranti et al, 1997;Lemeille et al, 1999;Delaby, 2001;Kagan et al, 2005;Šebela, 2008;Panno et al, 2009;Bábek et al, 2015;Méjean et al, 2015), blocks and ceiling collapses (e.g., Gilli, 1999;Pérez-López et al, 2009), deformed cave sediments and fault displacements (e.g., Gilli et al, 2010;Bábek et al, 2015), and speleothem growth anomalies (e.g., Forti et al, 1981;Forti and Postpischl, 1984;Akgöz and Eren, 2015;Rajendran et al, 2015). Although direct observations of cave damages immediately after an earthquake have rarely been observed, "seismothems" (i.e., speleothems potentially broken, or deformed, by a seismic…”
Section: Introductionmentioning
confidence: 99%
“…The use of speleotectonics for the recognition of paleoearthquakes is highly debated in the literature both because there are many possible breakdown causes that must be discounted (e.g., Gilli, 2005) and because the required conditions to break speleothems, in terms of speleothems vulnerability and seismic input, are still unclear (e.g., Cadorin et al, 2001;Lacave et al, 2004). On the other hand, peculiar features, recognized in many caves worldwide, have been often linked to earthquake damages (e.g., Postpischl et al, 1991;Ferranti et al, 1997;Lemeille et al, 1999;Delaby, 2001;Forti, 2001;Kagan et al, 2005;Šebela, 2008;Panno et al, 2009;Bábek et al, 2015;Méjean et al, 2015), although specific paleoearthquakes identified in caves have been rarely constrained by independent data outside caves (Becker et al, 2005). The speleotectonic analysis conducted in this study within the Cavallone Cave (in the most external portion of the Central Apennines) allowed for recognizing a mid-Holocene paleoearthquake and finding robust correlations with independent on-fault and off-fault data in surrounding areas.…”
Section: Discussionmentioning
confidence: 99%
“…Following some pioneering studies at the beginning of the 1990s (see Becker et al, 2006, for a review), many works have focused on the significance of cave damages and their possible correlations with active tectonics and, in particular, with the effects of seismic shaking. This evidence includes broken speleothems and fallen stalactites (e.g., Postpischl et al, 1991;Ferranti et al, 1997;Lemeille et al, 1999;Delaby, 2001;Kagan et al, 2005;Šebela, 2008;Panno et al, 2009;Bábek et al, 2015;Méjean et al, 2015), blocks and ceiling collapses (e.g., Gilli, 1999;Pérez-López et al, 2009), deformed cave sediments and fault displacements (e.g., Gilli et al, 2010;Bábek et al, 2015), and speleothem growth anomalies (e.g., Forti et al, 1981;Forti and Postpischl, 1984;Akgöz and Eren, 2015;Rajendran et al, 2015). Although direct observations of cave damages immediately after an earthquake have rarely been observed, "seismothems" (i.e., speleothems potentially broken, or deformed, by a seismic event; Delaby, 2001) have been increasingly recognized in many caves worldwide, allowing researchers to discover past earthquakes (see Becker et al, 2006, for a review).…”
Section: Introductionmentioning
confidence: 99%
“…If the support is made up of speleothems, such as stalactites, draperies and flowstones, the level of vulnerability is accentuated by their fragility, crystalline structure and laminated internal texture. The speleothems are highly fragile to vibrations caused by tremors, whether the cause is natural (earthquakes) or human (quarrying activity and blasting, for example) [21][22][23]. In Alkerdi caves the rock art is found on both types of supports: limestone rock walls (engravings and paintings) and on speleothems (paintings).…”
Section: Vulnerability Map (V)mentioning
confidence: 99%